THE REALIZATION OF EDUCATION AND TOLERANCE IN THE FRAME OF DIVERSITY THROUGH REOG PONOROGO FESTIVAL - Galih Puji Kurniawan; Silvi Sitaviana (AT-TAJDID, 2021)
The formulation of the problem was  why the Ponorogo Reog National Festival in a cultural tradition of Ponorogo Regency can be used as education and tolerance to realize the unity of domestic diversity. The reason the researcher did this research is because there is still a lack of research on the National Festival of Reog Ponorogo in our city. In addition, the researcher wants the cultural traditions in Ponorogo that have existed since time immemorial, one of which is the Reog National Festival. The purpose of this study is to find out about the Reog Ponorogo National Festival, a cultural tradition of Ponorogo Regency as an education and creator of tolerance to realize the unity of Diversity in the country. The theoretical basis that the researcher uses in this research is about Reog Ponorogo and the Reog National Festival because these two topics are relevant to our research. Our writing method is a qualitative method with data sources consisting of primary and secondary data. Data collection methods consist of literature study, interviews, and documentation. Our data collection instruments used interview lists and documentation guidelines. While the methods and techniques of data analysis that we use are qualitative. The result of our research is that the National Festival of Reog Ponorogo which is routinely held every 1 Suro other than the one used for the research turns out to provide positive values in the community, including education and tolerance.Keywords: Realization of Education, Realization of Tolerance, Reog Ponorogo as Tolerance